Immunomodulatory Effect of Dietary Nelumbo Nucifera (Lotus) in Growth and Haematology of Cirrhinus Mrigala Challenged With Pseudomonas Aeruginosa - A. Sivagurunathan, B. Xavier Innocent, S. Muthu lakshmi (Journal of Applied Pharmaceutical Science)
The present study was carried out to evaluate the immunostimulant potential of Nelumbo nucifera (Lotus). Formulated diets with different concentrations of ethanolic extract of N.nucifera (D1=0%, D2=1% and D3=2%) were fed to Cirrhinus mrigala for 40 days, the Specific Growth Rate (SGR) and Feed Conversion Ratio (FCR) were calculated significant increase was observed in SGR &FCR. Then the experimental fishes were infected with Pseudomonas aeruginosa and after 5 days the haematological parameters like Total Erythrocyte count (TEC), Haemoglobin (Hb), Total leucocyte count (TLC), Differential leucocyte count (DLC), serum total protein, serum albumin and globulin levels were analyzed. The TEC, Hb, TLC, Lymphocytes and monocyte counts increased significantly in D3 diet fed fishes. Highly significant increase was observed in serum total protein and albumin levels only. Globulin levels remain unchanged. Basophil and Eosinophil counts decreased significantly. Thus N.nucifera in fish feed preparations may be included as growth promoter and immunostimulator.
Keywords: Nelumbo nucifera, Cirrhinus mrigala, Pseudomonas aeruginosa, haematology, Immunostimulator